Family study of sensation seeking - Butković, Ana (Array, 2002)
Previous behaviour genetic studies of sensation seeking are suggesting substantional heritability estimates of this trait, ranging between 50-60%. However, the majority of these studies was done using twin design. The study reported here used a family design, and the sample consisted of highschool students and their parents: 151 offspring (95 females and 56 males), 148 mothers and 118 fathers. Both offspring and their parents completed Sensation Seeking Scale - Form V (SSS-V). Beside SSS-V, parents also completed the Parental Behaviour Scale (PBS). Parental Behaviour Scale is a measure of parental behaviour developed for the purpose of this research. It consists of 10 items measuring two dimensions of parental behaviour: parental affection and parental control. Each parent had to report his/her own behaviour, as well as the behaviour of their partners. Parents' SSS-V and PBS scores were related with the offspring's SSS-V scores. Father-offspring correlations ranged between 0.18 and 0.27 for different sensation-seeking subscales (Thrill and Adventure Seeking Scale - TAS ; Experience Seeking Scale - ES ; Disinhibition Scale - Dis ; Boredom Susceptibility Scale - BS), while mother-offspring correlations ranged between 0.02 and 0.24. Regressions of offspring on midparent scores ranged between 0.18 and 0.31. Mother-father correlations were statistically significant for all subscales, except for TAS subscale, and ranged between 0.26 and 0.46 suggesting assortative mating for sensation seeking in this sample. The only measure from Parental Behaviour Scale that correlated with children's sensation seeking was fathers' parental control (average fathers' control correlated 0.24 with total children's SSS score).